Needs and Experiences in Psychiatric Treatment (NEPT)- Piloting a Collaboratively Generated, Initial Research Tool to Evaluate Cross-Sectoral Mental Health Services - von Peter, Sebastian; Krispin, Helene; Kato Glück, Rosa; Ziegenhagen, Jenny; Göppert, Lena; Jänchen, Patrick; Schmid, Christine; Neumann, Anne; Baum, Fabian; Soltmann, Bettina; Heinze, Martin; Schwarz, Julian; et al. (Frontiers in Psychiatry, 2022)
Background: Research tools to evaluate institutions or interventions in the field of mental health have rarely been constructed by researchers with personal experience of using the men-tal health system (=experiential expertise). This paper presents a preliminary tool that has been developed within a participatory-collaborative process evaluation as part of a controlled, mul-ti-center, prospective cohort study (PsychCare) to evaluate psychiatric flexible and integrative treatment (=FIT) models in Germany. Method: The collaborative research team consisting of researchers with and without experien-tial expertise developed 12 experiential program components of FIT models by an iterative research process based on the Grounded Theory Methodology. These components were trans-formed into a preliminary research tool that was evaluated by a participatory expert panel, and during a pilot and validation study, the latter using a random sample of 327 users from 14 mental health departments. Internal consistency of the tool was tested using Cronbach's alpha. Construct validity was evaluated using a Principal Components Analysis (PCA) and a Jonck-heere Terpstra test in relation to different implementation levels of the FIT model. Concurrent validity was tested against a German version of the Client Satisfaction Questionnaire (ZUF-8) using correlation analysis and a linear regression model. Results: The evaluation of the expert panel reduced 29 initial items to 16 that were further re-duced to 11 items during the pilot study, resulting into a research tool (Needs and Experiences in Psychiatric Treatment - NEPT) that demonstrated good internal consistency (Cronbach’s alpha of 0.89). PCA yielded a 1-component structure, which accounted for 49% of the total variance supporting the unidimensional structure of the tool. The total NEPT score increased alongside the increasing implementation of the FIT model (p < 0.05). There was evidence (p < 0.001) for convergent validity assessed against the ZUF-8 as criterion measure. Conclusions: The NEPT tool seems to be promising for further development to assess the expe-riences with and fulfilment of needs of psychiatric care models from the perspective of users. This paper demonstrates that it is possible to use a participatory-collaborative approach within the methodologically rigorous confines of a prospective, controlled research design.